A loop-mediated isothermal amplification procedure targeting the sodA gene for rapid and specific identification of Gallibacterium anatis. (14th March 2018) - Stępień-Pyśniak, D; Kosikowska, U; Hauschild, T; Burzyński, A; Wilczyński, J; Kolińska, A; Nowaczek, A; Marek, A
Abstract: This paper reports on the development and validation of a real-time loop-mediated isothermal amplification assay (LAMP) for rapid and specific identification of Gallibacterium anatis . To design a set of 6 primers using the LAMP technique, the conserved region of the G. anatis sodA gene was selected as a target. To evaluate primer specificity we used 120 field strains, the reference strain G. anatis ATCC 43329, and 9 non- G. anatis bacteria. The results confirmed positive reactions for all G. anatis strains tested by LAMP at 63°C for 60 min, with no cross-reactivity observed for the negative control bacteria, i.e., Haemophilus parainfluenzae (ATCC 51505 and ATCC 33392), Aggregatibacter aphrophilus ATCC 7901, Avibacterium endocarditis, Pasteurella multocida, Actinobacillus pleuropneumoniae, Avibacterium paragallinarum, Ornithobacterium rhinotracheale, and Escherichia coli . The lowest detectable amount of DNA for the LAMP reaction was 0.2561 pg, which was detected in about 34 min, while the highest available concentration of the G. anatis reference strain was detected in about 10 min. The lowest detectable amount of DNA for the real-time PCR reaction was 21.24 pg, which was detected in about 20 min, while the highest available concentration of the G. anatis reference strain was detected in about 7 min. Moreover, using the real-time LAMP assay the reaction could be effectively carried out in a volume of just 13 μL, about half the officially recommended reaction volume (25 μL). The aim of this study was to develop a highly sensitive and specific G. anatis real-time LAMP assay that is less time-consuming and less costly than quantitative PCR.